Integrasi Ilmu Agama Dengan Ilmu Umum Untuk Menghadapi Era Globalisasi - Agus Miftakus Surur; Siti Mahmudah; Siti Nur Khasanah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
Science of religion and science of general importance that should be controlled by everyone in order to rule the world and also can control the hereafter. For the sake of balancing the General Science and religion science needs to make policies. Researchers explore or examine deeper against a problem of integration of science and religion science common to students in facing the globalization era in boarding schools Daughter Ar-Raudloh. The concept of integration of science and religion science the public looks at the latest innovation by integrating two different things, between religion and Science General Science of embodied language learning with the United Kingdom. For the application of the integration of religion and Science General Science by students in facing the era of globalization through additional language learning United Kingdom should ideally include, United Kingdom language learning planning process, the target to be achieved in the process of United Kingdom language learning, implementation and evaluation of language learning learning United Kingdom. There is no difference between the public school children only or in the lodge only. Keywords: integration, Religious knowledge, Public science, Globalization